Effect of sintering temperatures on corrosion and wear properties of sol-gel alumina coatings on surface pre-treated mild steel - Ruhi G.; Modi O.P.; Sinha A.S.K.; Singh I.B. (My University, 2025)
Sol-gel alumina coatings were developed on the surface pre-treated (zinc-phosphated) mild steel substrate and subsequently sintered at 300 °C, 400 °C and 500 °C. The alumina sol was synthesised using aluminium iso-propoxide as a precursor material. FTIR of the boehmite (AlOOH) gel sintered at above-mentioned temperatures was employed to identify the presence of various functional groups. The microstructural features and the phase analysis of the sol-gel coated specimens were carried out using SEM and XRD respectively. The corrosion resistance of the sol-gel alumina coatings was evaluated by electrochemical measurement in 3.5% NaCl solution at room temperature. The abrasive wear behaviour of the sol-gel coated specimens was measured in two body (high stress) conditions. The experimental results revealed that the sol-gel coated specimen sintered at 400 °C has superior wear and corrosion resistance properties as compared to the sol-gel coated specimen sintered at 300 °C. However, the sol-gel coated specimen sintered at 500 °C has exhibited a very poor corrosion and wear resistance properties. Poor performance of the sol-gel coatings sintered at 500 °C could be explained to be due to (i) the presence of numerous cracks (ii) absence of organic groups in the coating. © 2007 Elsevier Ltd. All rights reserved.